2017
DOI: 10.2196/jmir.8106
|View full text |Cite
|
Sign up to set email alerts
|

What is eHealth (6)? Development of a Conceptual Model for eHealth: Qualitative Study with Key Informants

Abstract: BackgroundDespite rapid growth in eHealth research, there remains a lack of consistency in defining and using terms related to eHealth. More widely cited definitions provide broad understanding of eHealth but lack sufficient conceptual clarity to operationalize eHealth and enable its implementation in health care practice, research, education, and policy. Definitions that are more detailed are often context or discipline specific, limiting ease of translation of these definitions across the breadth of eHealth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
205
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(240 citation statements)
references
References 23 publications
(28 reference statements)
6
205
0
13
Order By: Relevance
“…eHealth can be broadly defined as the integration of devices, communication, and data in healthcare [7]. The use of eHealth tools such as web-portals (WPs), wearable activity trackers, and personalised text and email messaging may increase the capacity for delivering individualised, scalable, and costeffective physical activity-based behavioural change initiatives in this population.…”
Section: Ehealth and Web-based Portalsmentioning
confidence: 99%
“…eHealth can be broadly defined as the integration of devices, communication, and data in healthcare [7]. The use of eHealth tools such as web-portals (WPs), wearable activity trackers, and personalised text and email messaging may increase the capacity for delivering individualised, scalable, and costeffective physical activity-based behavioural change initiatives in this population.…”
Section: Ehealth and Web-based Portalsmentioning
confidence: 99%
“…The integration of telehealth and other web‐based technologies into the delivery of healthcare is an area of rapid growth internationally (Dorsey & Topol, ; Meier, Fitzgerald, & Smith, ; Michie, Yardley, West, Patrick, & Greaves, ; Weinstein et al, ). These methods are commonly referred to as electronic healthcare or e‐Health, but a consensus definition for what e‐Health specifically refers to is lacking (Oh et al, ; Shaw et al, ). In an earlier systematic review on the definition of e‐Health, Oh et al () found that definitions of e‐Health in the literature varied from straight‐forward explanations such as ‘the integration of the internet into health care’ to more complex definitions including: ‘E‐Health is an emerging field focused on… health care services delivered… through advanced Internet or related technologies’.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier systematic review on the definition of e‐Health, Oh et al () found that definitions of e‐Health in the literature varied from straight‐forward explanations such as ‘the integration of the internet into health care’ to more complex definitions including: ‘E‐Health is an emerging field focused on… health care services delivered… through advanced Internet or related technologies’. A recent review by Shaw et al () suggests this lack of consistent definition has persisted and proposes that e‐Health definitions be framed around three overlapping domains, broadly discussed as (a) self‐management, (b) interacting and (c) data enabling. In line with this framework, we have defined e‐Health in this study as technologies that enable assessment and disease management either with provider‐patient interaction or entirely patient‐driven.…”
Section: Introductionmentioning
confidence: 99%
“…E-health was also defined as internet-based health-related information seeking and developing to support health services locally, regionally, and globally [8]. E-health was recently defined by Shaw et al [9] as an emerging field in the intersection of medical informatics, public health, and business. The term characterizes not only a technical development, but also a state-of-mind, a way of thinking, an attitude, and a commitment for networked global thinking, to improve healthcare locally, regionally, and worldwide by using information and communication technology (ICT).…”
Section: Introductionmentioning
confidence: 99%